Risk Factor Analysis of Maxillary Sinus as Sinusitis with The Highest Incidence - Adji, Iwan Setiawan; Widoningrum, Farha Nabila (Konsorsium LPPM Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2023)
Sinusitis is an inflammatory disease of the paranasal sinus cavities that can be caused by infection, allergies, or autoimmune problems, and is a disease that is often found in everyday medical practice and is even considered one of the most common causes of health problems in the world. Epidemiologically, the maxillary sinuses are most commonly affected, then the ethmoidal, frontal, and sphenoidal which are included in the acute sinusitis section. The purpose of this literature review is to collect and synthesize articles describing the maxillary sinus as sinusitis with the highest incidence and to find out the underlying risk factors. This literature review method is done by searching for references in databases and search engines with keywords and then synthesizing the results in the form of a narrative. The results we get can be concluded that the maxillary sinus is the most frequently infected paranasal sinus due to various factors such as the size of the paranasal sinus being the largest, the location of the ostium being higher than the base, the ostium located in the meatus medius, around the hiatus semilunaris which is narrow so it gets easily blocked, and The maxillary sinus is the base of the tooth root (alveolar process) so that dental infection can cause odontogenic maxillary sinusitis in adulthood.